Consented Violence in Mesopotamia: from Factuality to Representation - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
It is intricate to give a definition of violence as large as all the domains concerned. It’s not only a formal question, it involves also questions and answers evoked by the different concepts of violence. Is violence inherent to humans and so excusable at least in part? Is violence only the extreme outcome of a more or less ‘normal aggressive human behaviour’? Is there a structural violence? Is violence rational or emotional?